The Acceptance of Digital Health: What about Telepsychology and Telepsychiatry? - Anas Alhur; Arwa Ali Alhur (Jurnal Sistem Informasi, 2022)
Electronic health is a solution for many issues. This study aims to determine the acceptance level of telepsychology and telepsychiatry services their advantages and disadvantages. The researchers carried out a cross-sectional study. Results indicate that only 13.3% of respondents visited a psychiatrist or psychologist. The majority views telepsychiatry and psychological services as beneficial tools that enhance privacy. According to the survey, 223 respondents believe they have a psychological problem. The most common disorders are general anxiety, social anxiety, and depression. Most of their families accept mental health treatment, and four respondents lack access to electronic devices and the Internet. The security and privacy of patient's information should be investigated further in telepsychology and telepsychiatry. Our research may influence decision-makers to invest in this area for the benefit of society.